Territoires – Identités – Patrimoine : une approche économique ? - Denis Requier-Desjardins (Développement Durable et Territoires)
Place is not at first sight an economic concept; mainstream spatial economics remains largely unconcerned by Place. Economics has taken an interest in it in the last twenty years. This paper deals with the role of place in economic analysis, and its relationship with the concepts of heritage and identity. Elaborated by heterodoxy and institutionalism in economics, it has been sometimes criticised by economists belonging to these very persuasions. We sustain that only qualifications processes of goods and assets in production and consumption give it an endogenous status as a marker of a quality characteristic. Actually qualification processes implies references to heritage and identity. The building of a territorial identity requires the collective action of place-specific groups who set up the heritage character of some exclusive resources. This largely questions the approach of a given heritage and identity.